A plausible role for actin gamma smooth muscle 2 (ACTG2) in small intestinal neuroendocrine tumorigenesis. Issue 1 (December 2016) - Edfeldt, Katarina; Hellman, Per; Westin, Gunnar; Stalberg, Peter
Abstract Background Small intestinal neuroendocrine tumors (SI-NETs) originate from the enterochromaffin cells in the ileum and jejunum. The knowledge about genetic and epigenetic abnormalities is limited. Low mRNA expression levels of actin gamma smooth muscle 2 (ACTG2 ) have been demonstrated in metastases relative to primary SI-NETs.ACTG2 and microRNA-145 (miR-145) are aberrantly expressed in other cancers andACTG2 can be induced by miR-145. The aim of this study was to investigate the role ofACTG2 in small intestinal neuroendocrine tumorigenesis. Methods Protein expression was analyzed in SI-NETs (n  = 24) and in enterochromaffin cells by immunohistochemistry. The cell line CNDT2.5 was treated with the histone methyltransferase inhibitor 3-deazaneplanocin A (DZNep), the selective EZH2 inhibitor EPZ-6438, or 5-aza-2'-deoxycytidine, a DNA hypomethylating agent. Cells were transfected withACTG2 expression plasmid or miR-145. Western blotting analysis, quantitative RT-PCR, colony formation- and viability assays were performed. miR-145 expression levels were measured in tumors. Results Eight primary tumors and two lymph node metastases displayed variable levels of positive staining. Fourteen SI-NETs and normal enterochromaffin cells stained negatively. Overexpression ofACTG2 significantly inhibited CNDT2.5 cell growth. Treatment with DZNep or transfection with miR-145 inducedACTG2 expression (>10-fold), but no effects were detected after treatment with EPZ-6438 or 5-aza-2'-deoxycytidine. DZNep also induced miR-145 expression. SI-NETs expressed relatively low levels of miR-145, with reduced expression in metastases compared to primary tumors. Conclusions ACTG2 is expressed in a fraction of SI-NETs, can inhibit cell growth in vitro, and is positively regulated by miR-145. Theoretical therapeutic strategies based on these results are discussed.